Anti-Vascular Endothelial Growth Factor (Anti-VEGF) in Central Retinal Vein Occlusion : Are Loading Dose Necessary ? - Andi Arus Victor (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2019)
Background : Ranibizumab (anti-VEGF) given monthly for six doses, is effective in central retinal vein occlusion (CRVO). However, the cost and adherence to complete Ranibizumab regiment is a burden for developing countries. Aim : To present two CRVO cases with satisfactory outcome after partial regiment of ranibizumab injections. Case presentation : A 52-year old male came with sudden, painless visual decline of the left eye (LE). Best corrected visual acuity (BCVA) was 0.4. Relative afferent pupillary defect (RAPD) was positive on LE. Anterior segment was normal. Fundus examination revealed a cup-disc ratio (CDR) of 0.4, macular edema (ME), scattered hemorrhages, dilated and tortuous retinal veins. Patient was diagnosed with CRVO and was given two monthly injections before stopping treatment. Patient came with worsened VA, was then given another injection. After 6 months, his BCVA was 0.8. Similarly, a 32- year old male came with sudden painless decline of vision of LE (BCVA 0.15). Anterior segment was normal. Fundus examination showed CDR of 0.3, ME, multiple scattered pre-retinal hemorrhages, dilated and tortuous retinal veins. Patient was similarly diagnosed with CRVO of LE and given two monthly injections. Final BCVA after six months follow-up was 0.9. Conclusion : Both cases showed improvement in VA despite having partial regiment of ranibizumab injections.